Incidence of Vertigo distribution among young adult and elderly in patients attending Al-Diwaniya Teaching Hospital . Al-Diwaniya. - Yousef, Raid Yaqoub; humady, Ahmed (AL-Kindy College Medical Journal, 2013)
This study is prospective in nature, It consider 110 patients with vertigo who were assessed between April and December 2010 at E.N.T out patient department of otolarygiology, in Al Diwania teaching hospital, in Diwania city, Iraq. The study is designed to assess the incidence of vestibular and non vestibular vertigo and their association with tinnitus,hearing loss,migraine in Young adult and elderly.All patients were assessed by questionary method and by pure tone Audiometry. Results: the incidence of vestibular vertigo was 69.1% while non vestibular vertigo is 30.9 %, vestibular vertigo was inversely related to the age while non vestibular vertigo directly related to the age The percentage of association between tinnitus, migraine, hearing loss with vestibular and non vestibular vertigo were 71%,6%),(29%,35%),(74%,18%) correspondingly. Conclusion; vestibular vertigo was more common than non vestibular vertigo in young adult and elderly, and it is significantly associated with tinnituswith migraine.